General and Modular Strategy for Designing Potent, Selective, and Pharmacologically Compliant Inhibitors of Rhomboid Proteases. Issue 12 (21st December 2017) - Tichá, Anežka; Stanchev, Stancho; Vinothkumar, Kutti R.; Mikles, David C.; Pachl, Petr; Began, Jakub; Škerle, Jan; Švehlová, Kateřina; Nguyen, Minh T.N.; Verhelst, Steven H.L.; Johnson, Darren C.; Bachovchin, Daniel A.; et al.
Summary: Rhomboid-family intramembrane proteases regulate important biological processes and have been associated with malaria, cancer, and Parkinson's disease. However, due to the lack of potent, selective, and pharmacologically compliant inhibitors, the wide therapeutic potential of rhomboids is currently untapped. Here, we bridge this gap by discovering that peptidyl α-ketoamides substituted at the ketoamide nitrogen by hydrophobic groups are potent rhomboid inhibitors active in the nanomolar range, surpassing the currently used rhomboid inhibitors by up to three orders of magnitude. Such peptidyl ketoamides show selectivity for rhomboids, leaving most human serine hydrolases unaffected. Crystal structures show that these compounds bind the active site of rhomboid covalently and in a substrate-like manner, and kinetic analysis reveals their reversible, slow-binding, non-competitive mechanism. Since ketoamides are clinically used pharmacophores, our findings uncover a straightforward modular way for the design of specific inhibitors of rhomboid proteases, which can be widely applicable in cell biology and drug discovery. Graphical Abstract: Highlights: N-substituted peptidyl α-ketoamides are nanomolar inhibitors of rhomboid proteases Peptidyl ketoamides inhibit rhomboids covalently, reversibly, and non-competitively The peptide and ketoamide substituent independently modulate potency and selectivity Peptidyl ketoamides are selective for rhomboids, sparing most human serine proteases Abstract : Ticha et al. discover rhomboid protease inhibitors that are unprecedentedly potent and selective. They are based on a pharmacologically compliant chemotype and can thus serve as hitherto unavailable specific tools for cell biology or can yield lead compounds targeting rhomboids in medically relevant contexts such as malaria or Parkinson's disease.